Dijets at Tevatron cannot constrain SMEFT four-quark operators - Eduard Keilmann; William Shepherd (Journal of High Energy Physics, 2019)
Abstract We explore the sensitivity of Tevatron data to heavy new physics effects in differential dijet production rates using the SMEFT in light of the fact that consistent and conservative constraints from the LHC cannot cover relatively low cutoff scales in the EFT. In contrast to the results quoted by the experimental collaborations and other groups, we find that, once consistency of the perturbation expansion is enforced and reasonable estimates of theoretical errors induced by the SMEFT series in E Λ $$ \frac{E}{Λ} $$ are included, there is no potential to constrain four-quark contact interactions using Tevatron data. This shows the general difficulty of constraining physics model-independently using fairly imprecise measurements, limited by low luminosity and/or systematic errors inherent to the precision of the detectors.